2010
DOI: 10.1111/j.1365-2141.2010.08492.x
|View full text |Cite
|
Sign up to set email alerts
|

Allogeneic transplantation for Hodgkin’s lymphoma

Abstract: SummaryHodgkin's lymphoma (HL) can be cured in most of the patients, but in case of refractory disease or relapse after autologous stem cell transplantation (SCT) the prognosis becomes very poor. In these patients a consensus about the standard approach has not been achieved so far and only allogeneic SCT has shown a long-term disease control. The postulated graft-versus-Hodgkin's lymphoma is a matter of controversy, but the clinical responses observed after donor lymphocyte infusions may explain the superiori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 78 publications
0
19
0
1
Order By: Relevance
“…The clinical response, observed after chemotherapy and donor lymphocyte infusions, together with a high number of patients who remain in CR with a 63% disease-free survival at 4 years, would suggest the existence of a graft-versus-Hodgkin's lymphoma effect, operating in the setting of haplo-transplants and PT-CY. 24,25 An additional comment should be made on our experience with DLI: the lack of GvHD following several DLI, as well as the very low overall rate of GvHD, would point to allogeneic tolerance, actively maintained by regulatory T cells, without counteracting GvL.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical response, observed after chemotherapy and donor lymphocyte infusions, together with a high number of patients who remain in CR with a 63% disease-free survival at 4 years, would suggest the existence of a graft-versus-Hodgkin's lymphoma effect, operating in the setting of haplo-transplants and PT-CY. 24,25 An additional comment should be made on our experience with DLI: the lack of GvHD following several DLI, as well as the very low overall rate of GvHD, would point to allogeneic tolerance, actively maintained by regulatory T cells, without counteracting GvL.…”
Section: Discussionmentioning
confidence: 99%
“…Demonstrated responses to donor lymphocyte infusion (DLI) and a trend toward a lower relapse rate after allogeneic SCT than after ASCT, especially when chronic graft-versus-host disease (GVHD) occurs, are direct and indirect arguments for a GVHL effect. [37][38][39] Because of the negative aspect of treatment-related mortality (TRM) of myeloablative conditioning regimens, reduced intensity conditioning (RIC) regimens have emerged as a potential option with acceptable TRM and long-term response. 40,41 Importantly, several studies have shown that chemosensitivity at transplantation remains a major predictor of outcome of RIC allogeneic SCT (RIC-allo).…”
Section: Allogeneic Stem-cell Transplantationmentioning
confidence: 99%
“…40,41 Importantly, several studies have shown that chemosensitivity at transplantation remains a major predictor of outcome of RIC allogeneic SCT (RIC-allo). 38,41,42 The expert panel acknowledges that RIC-allo may have a role in HL. For patients with primary refractory disease, and for those relapsing after first-line standard-dose chemotherapy, RIC-allo without previous ASCT is not recommended.…”
Section: Allogeneic Stem-cell Transplantationmentioning
confidence: 99%
“…[16][17][18] Following the failure of allo-SCT, treatment options are limited and the prognosis for patients at this stage is extremely poor. 19 There is therefore a need for new therapeutic options for HL patients with relapsed/refractory disease. sALCL is a rare type of non-HL (NHL), and represents a group of large cell lymphomas, distinguished from other lymphomas by its anaplastic cytology and constant membrane expression of the CD30 antigen.…”
Section: Current Standard Of Care In Hodgkin's Lymphoma and Systemic mentioning
confidence: 99%